Design and thermodynamic analysis of a hybrid energy storage system based on A-CAES (adiabatic compressed air energy storage) and FESS (flywheel energy storage system) for wind power application - Zhao, Pan; Dai, Yiping; Wang, Jiangfeng (Energy (Oxford), 2014)
Electricity generated from renewable wind sources is highly erratic due to the intermittent nature of wind. This uncertainty of wind power can lead to challenges regarding power system operation and dispatch. Energy storage system in conjunction with wind energy system can offset these effects, making the wind power controllable. Moreover, the power spectrum of wind power exhibits that the fluctuations of wind power include various components with different frequencies and amplitudes. Thus, the hybrid energy storage system is more suitable for smoothing out the wind power fluctuations effectively rather than the independent energy storage system. A hybrid energy storage system consisting of adiabatic compressed air energy storage (A-CAES) system and flywheel energy storage system (FESS) is proposed for wind energy application. The design of the proposed system is laid out firstly. The A-CAES system operates in variable cavern pressure, constant turbine inlet pressure mode, whereas the FESS is controlled by constant power strategy. Then, the off-design analysis of the proposed system is carried out. Meanwhile, a parametric analysis is also performed to investigate the effects of several parameters on the system performance, including the ambient conditions, inlet temperature of compressor, storage cavern temperature, maximum and minimum pressures of storage cavern. •A wind-hybrid energy storage system composed of A-CAES and FESS is proposed.•The design of the proposed hybrid energy storage system is laid out.•The off-design analysis of the proposed system is carried out.•A parametric analysis is conducted to examine the system performance.